1992
DOI: 10.1002/iroh.19920770106
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrogen Cycle in Lough Neagh, N. Ireland 1975 to 1987

Abstract: Results from thirteen years of weekly observations are presented on the nitrogen cycle in Lough Neagh. The data comprised catchment and atmospheric inputs, output via the outflow and calculated losses by sedimentation and denitrification. Nitrate-nitrogen in the rivers is the dominant input fraction and the nitrate loading has increased over the period observed. 52 % of the input N sediments to the lake bottom, but 65 % of this is lost by denitrification. In spite of increasing nitrogen inputs, the summer solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
3
4
0
Order By: Relevance
“…in relation to external quarterly load to be low during the first quarter of the year (23%), three times higher during the third quarter and intermediate during the second and fourth quarters. In terms of absolute retention a similar seasonal pattern has been reported for Tegeler See by Rip1 & Feibicke (1992) and by Gibson et al (1992). In shallow lake Diimmer, in contrast, Rip1 & Feibicke (1992) found retention to be maximum in early spring and low during summer (during which time there was a concurrent distinct reduction in the Nload), while Andersen (1974) and Bengtsson (1978) found no clear seasonal pattern in Nret .…”
Section: Introductionsupporting
confidence: 62%
“…in relation to external quarterly load to be low during the first quarter of the year (23%), three times higher during the third quarter and intermediate during the second and fourth quarters. In terms of absolute retention a similar seasonal pattern has been reported for Tegeler See by Rip1 & Feibicke (1992) and by Gibson et al (1992). In shallow lake Diimmer, in contrast, Rip1 & Feibicke (1992) found retention to be maximum in early spring and low during summer (during which time there was a concurrent distinct reduction in the Nload), while Andersen (1974) and Bengtsson (1978) found no clear seasonal pattern in Nret .…”
Section: Introductionsupporting
confidence: 62%
“…The trends of water column N depletion and release of sediment P were determined. The month within which the NOx concentration fell below 0.06mg/L was identified; Gibson et al (1992) found that the summer (July-September) average nitrate concentration fell from 0.20 to <0.05mg/L over the 1971 to 1980 period, so 0.06mg/L was chosen as a threshold for the depletion of NOx through assimilation by phytoplankton. We also identified the month that the SRP concentration began to increase above 0.010mg/L (where the previous month was below this value) and this was the threshold used to indicate the start of sediment P release as described by Gibson and Stewart (1993).…”
Section: Lake Nutrient Loading and Sediment Releasementioning
confidence: 99%
“…A time series of nitrate exports are presented for the Blackwater River, which was sampled and analysed for nitrate (total inorganic N) weekly from 1971 to 2007 as set out by Gibson et al. (1988, 1992).…”
Section: Study Site Limnology and Documentary Datamentioning
confidence: 99%
“…A time series of nitrate exports are presented for the Blackwater River, which was sampled and analysed for nitrate (total inorganic N) weekly from 1971 to 2007 as set out by Gibson et al ( , 1992. Loadings are presented for the hydrological year beginning in October, so that the hydrological year for 1972 begins on 1 October 1971.…”
Section: Land-cover Change and Intensity Of Farmingmentioning
confidence: 99%
See 1 more Smart Citation